PELAKSANAAN ASAS KEBEBASAN BERKONTRAK TERHADAP PERJANJIAN FRANCHISE DI SAMARINDA - Kristiyono Condro wiyoso (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTIn the Indonesian economy, one area that stands out is the field of trade. It has three principal activities of the economic system, namely Production, Distribution and Consumption. One way of distributing the business expands internationally is through licensing, as an alternative attempt to get closer to consumers in the host country as well as to reduce the impact of high export transport costs, as well as the risk of loss of product from the market as a result of transportation risks and possible embargo done politically.